Assessment Of The Need For A Lashing Officer On A France Ship At Tanjung Kalian-Tanjung Api-Api Province Of Bangka Belitung - Sri Kartini; Ferdinand Pusriansyah; Adani Fairul Zabadi (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2022)
Human Resource Management is one of the fields of study that is very important in good and orderly management of agencies. Personnel management is planning, organizing, directing, supervising the activities of procurement, development, compensation, integration, maintenance of employees or employees in order to achieve individual, organizational, and community goals. The need for special lashing officers at the Tanjung Kalian Crossing Port is not yet available and poses a risk for ships that want to sail because the cargo is not lashed. This study uses a quantitative approach. The theory used is analysis in the special calculation of workloads. The results of this study indicate that each ship operating at the Tanjung Kalian Crossing Port averages 2-3 ships. Based on the workload analysis, it was found that each lashing officer has a workload of 14 hours per day. This is known considering that services at Tanjung Kalian Ferry Port have high productivity with trips available every day. Thus, the need for lashing officers at the Tanjung Kalian Ferry Port is urgently needed considering the tight schedule and high passenger productivity and affect the stability of the operating ship.